The New Republic
This editorial from The New Republic, titled "Calling All Delegates," urges Democratic convention delegates to reject Hubert Humphrey's nomination in 1968, arguing that the party faces a profound political and moral crisis. It contends that Humphrey's close association with the Johnson administration and the Vietnam War has alienated voters, particularly young people and those mobilized in the primaries by Eugene McCarthy and Robert Kennedy. The article criticizes the coalition backing Humphrey—including party bosses, Southern segregationists, labor leaders, and wealthy donors—portraying their strategy as undemocratic and reliant on fear of a Nixon victory. It warns that nominating Humphrey could deepen public disillusionment, provoke social unrest, and weaken the Democratic Party both morally and electorally. The editorial calls on delegates to heed the popular demand for change, suggesting that only a candidate such as McCarthy could restore public trust and broaden support among independents and reform-minded voters.